The Influence of STEAM-Based Learning Application on Students' Critical Thinking Ability - Muhammad Syukri; Zhaifatul Ukhaira; zainuddin zainuddin; Fitria Herliana; Nurazidawati Mohamad Arsad (Asian Journal of Science Education, 2022)
The learning process in Indonesia has not directed students to be able to think at a high level which resulted in the quality of education in Indonesia is still quite low. This study aims to determine the effect of the application of STEAM-based learning on students' critical thinking skills. This research is a "pree experimental design with one group pretest-posttest design" study. The population of this study were all students of class XI IPA, totaling 3 classes. Sampling was done by means of simple random sampling so that the students of class XI IPA 1 SMAN 1 Baitussalam were obtained. The data collection technique used is a test question (pretest and posttest). The results showed that the Pre-test score obtained was a minimum of 5 and a maximum value of 50, while the Post-test score of at least 60 and a maximum value of 95, the average improvement of students on the final test was more than the average score of the pretest. The results of data analysis showed the value of Sig. (2-tailed) value 0.000 0.05. This shows that H0 is rejected which indicates that there are differences in students' critical thinking results. This shows an increase in students' critical thinking through the application of a STEAM-based learning approach. These differences can be caused by differences in the learning approaches used, where in the post-test using the STEAM approach, during the learning process students are faced with a problem that must be solved with their respective group friends. In addition, students must be able to connect science concepts with concepts found in everyday life. Based on the results of the research obtained, it shows that there is a significant effect of implementing STEAM-based learning on students' critical thinking skills.